Distributed Leadership in Secondary Schools: Possibilities and Impediments in Bangladesh - Salahuddin, Abu Nayeem Mohammad (Arts Faculty Journal, 2012)
Effective school leadership is a basic tenet for successful school since the outcome of a school depends on the quality of leadership. As a current popular form of leadership, distributed leadership focuses on the leadership of all team members in a school. Research shows that successful leadership depends on the context and time of a school. This paper tries to conceptualize distributed leadership in Bangladesh context during the time of their education restructuring. Though distributed leadership is seldom discussed and operated in developing countries, it advocates the implementation in those contexts due to the continuous success of it in the developed world. Hence, this conceptual paper discusses the possibilities and the potential problems in relation to implement this leadership form for the reforming education sector of Bangladesh. Prior to this, the theoretical background of distributed leadership has been considered in this article. To develop and deliver distributed leadership in Bangladesh, this paper suggests for initiating training programme for head teachers which should focus on long term positive change in education. DOI: http://dx.doi.org/10.3329/afj.v4i0.12930 The Arts Faculty Journal Vol.4 July 2010-June 2011 pp.19-32